PENGARUH LINGKUNGAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. AMTEK PRECISION COMPONENTS BATAM - Frida Elisabet Napitupulu; Ade Parlaungan Nasution (Universitas Riau Kepulauan, 2016)
Based on the background described in the work environment and work experience is the mostof one important thing is inside a company, to make the company can achieve the main goals of which is owned by the company. The purpose of this research is to discover how the influence of Work Environment and Work Experience for Employee Performance PT.Amtek Precision Components Batam. besides that, the researchers tested the hypothesis that the Work Environment influence on Employee Performance and Work Experience effect on Employee Performance. The research was conducted by means of a questionnaire or questionnaires completed by employees PT. Amtek Precision Components Batam. The results from this study that the Working Environment (X1) the significance value that is equal to 0.000, Work Experience(X2) of significance value is equal to 0.000. obtained value of R Square (R2) of 0.613 or 61,30%. This means the ability variable Work Environment, and Work Experience in explaining the Performance of employees is 61,30%. The remaining amount of 38,70% is explained by other variables that are not included in this study.The results of this study can be used by future researchers, as materials science research on Work Environment and Work Experience on Employee Performance.